PENGARUH MODAL INTELEKTUAL PENGELOLA REKSA DANA TERHADAP RETURN DAN RISIKO REKSA DANA SAHAM DI INDONESIA PADA TAHUN 2019 - Rasyid, Izzan; Ferli, Ossi (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to help beginner mutual fund investors in analyzing equity funds by knowing the characteristics of fund managers who tend to manage equity funds with outperforming performance and can minimize the total risk of the equity funds they have managed. The lack of knowledge on how to manage their funds is one of the reasons why investors choose equity funds. However, there is not a guarantee that the equity fund will have a better performance than the market. So that investors can suffer losses if they choose the wrong equity fund which was managed by the incompetent investment manager. This study uses a sample of 431 professional fund managers from 68 equity funds with outperforming performance in 2019.Using the multiple linear regression analysis method, this research has the results that a fund manager who has an economic education or having a CFA certification, can increase the value of excess return. Besides, by having a background in economic education, these managers can reduce the total risk of equity mutual funds they manage. However, the more experienced fund manager tends to have a higher total risk and a lower value of the excess return.Meanwhile, there are insignificant results on the value of excess return and the risk of equity funds if the fund manager has a technical education background or completing his education in the top 10 universities in Indonesia.